Bimbingan Sosial Bagi Anak Pelaku Tindak Pidana Kekerasan Seksual - Hendrik Antonius Tinambunan (Widya Yuridika, 2021)
Children are vulnerable to a period of biological, social and psychological change, which links children to the changing thoughts and feelings about themselves and community relations. Children's self-change is a positive change to make children more directed and to obey the norms and values that are in the community. In the number of children involved when behaving which is disturbing for all groups, not only the family but the environment and even the country.There are various factors that cause children to commit a crime. Children who behave badly, cannot be blamed completely for their mistakes. This behavior must be understood what makes children able to do that. The tendency of children to commit crime will fail to behave socially normal. The last resort in a child criminal process is detention. Children will be educated by correctional officers given guidance. Approach to children who are dealing with the law with efforts to become individuals who have positive character. The effort taken is to make a good approach to children. The approach of not using verbal violence does not force children to be more open about what happens to children. This is done by giving help to children to overcome problems, motivate children to be better.